Hypertension and Diabetes as a risk factor for dementia: a cross sectional study - Yahya, Arshad; Shamim, Robina; Anand, Kuljeet S. (International Journal of Research in Medical Sciences, 2019)
Background: A relation between possible cardiovascular risk factors (hypertension and diabetes) and dementia has been studied in the past and an association has been documented, in spite of some studies pointing to the contrary. Our purpose is to analyze the relation between these risk factors and dementia and add some information to the existing concept and will try to conceptualize the pathogenesis of dementia. Methods: This was a cross sectional study. Patients were recruited from amongst those presenting to our department by convenient consecutive sampling method after taking consent. Five hundred patients of different types of dementia were enrolled. Hypertension was diagnosed using JNC7 criteria. World health organization (WHO) diagnostic criteria were used to diagnose diabetes mellitus. The open Epi software version 3 was used to find the absolute values after preparing 2×2 table. Continuous quantitative data were analyzed using chi square test. Odds ratio and Risk ratio were also calculated. For all statistical tests, a p Value less than 0.05 was taken to indicate significance. Results: Study provides the strong positive association of hypertension (HTN) and diabetes mellitus (DM) with vascular dementia (VaD) but the relationship of these risk factors were not positively correlated with other dementia. Conclusions: Positive association of these risk factors with vascular dementia were found but not with the other types of dementia.